2018
DOI: 10.2174/1874364101812010226
|View full text |Cite
|
Sign up to set email alerts
|

Development of In Vitro Methodologies to Investigate Binding by Sodium Hyaluronate in Eye Drops to Corneal Surfaces

Abstract: Purpose:To develop in vitro methods to assess binding by sodium hyaluronate in eye drops to corneal surfaces.Methods:Two different, complementary corneal binding set-ups were developed. In a dynamic in vitro model, confluent corneal epithelial cells (HCE-T) were assembled in chamber slides and a declining channel. A static model was constructed with ex vivo porcine corneas clamped in Franz cells. To test the predictive capacity of models, four different eye drops containing sodium hyaluronate were spiked with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…These results are consistent with previous reports. 31,36 More importantly, our results also confirmed that SH could markedly enhance autophagy in CEI model cells.…”
Section: Discussionsupporting
confidence: 78%
“…These results are consistent with previous reports. 31,36 More importantly, our results also confirmed that SH could markedly enhance autophagy in CEI model cells.…”
Section: Discussionsupporting
confidence: 78%
“…To develop ocular drops that properly adhere to the cornea, both the cornea surface and the tear film must be considered and kept stable and consistent over time. Instillation of a formulation can disrupt the tear film over time and lead to cell damage that consequently causes conditions such as dry eye disease [ 35 ]. Surface tension allows us to understand the stability of the tear film and the tear film break-up time, which influences the eye drops’ spreading ability and adherence [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…This means that NADES formulations present hydrophilic properties, which are necessary for their application as ophthalmic solutions. Bock et al [ 35 ] used the sessile drop method to test four commercial eye drops on three different surfaces. A hydrophobic polyethylene terephthalate, such as PTFE, was used, as well as glass, which is hydrophilic, and cell monolayers of human corneal epithelial cells.…”
Section: Resultsmentioning
confidence: 99%